Polar confinement of Saturn's magnetosphere revealed by in situ Cassini observations. Issue 4 (24th April 2014) - Pilkington, N. M.; Achilleos, N.; Arridge, C. S.; Masters, A.; Sergis, N.; Coates, A. J.; Dougherty, M. K.
<x xml:space="preserve">Abstract</x> Plasma rotation plays a large role in determining the size and shape of Saturn's disk‐like magnetosphere. A magnetosphere more confined to the equator in the polar regions is expected as a result of the interaction between this type of obstacle and the solar wind. In addition, at times away from equinox, a north‐south asymmetry is expected where the magnetopause will be further confined in one hemisphere but less confined in the opposite hemisphere. Examining the extent of this confinement has been limited by a lack of high‐latitude spacecraft observations. Here for the first time, direct evidence for polar confinement of Saturn's magnetopause has been observed using in situ data obtained by the Cassini spacecraft during a series of high‐inclination orbits between 2007 and 2009. Following techniques established by previous authors, we assume an equilibrium between the solar wind dynamic pressure (which Cassini is generally unable to measure directly), and the magnetic plus plasma pressure inside the magnetosphere. This assumption thus allows us to estimate the upstream solar wind dynamic pressure (DP) for a series of magnetopause crossings, and hence to determine the expected location and global shape of the magnetopause as a function of DP. A clear divergence from the familiar axisymmetric models of the magnetosphere is observed, which may be characterized by an "apparent flattening parameter" of 0.81+0.03/−0.06 (representing a simple dilation of the nominal axisymmetric boundary along the ZKSM axis such that the extent is reduced by approximately 19% in this direction). This figure is insensitive to variations in DP.